Delayed Senescence and Marketability Index Preservation of Blackberry Fruit by Preharvest Application of Chitosan and Salicylic Acid - Martínez-Camacho, Joel Ernesto; Guevara-González, Ramón Gerardo; Rico-García, Enrique; Tovar-Pérez, Erik Gustavo; Torres-Pacheco, Irineo (Frontiers in Plant Science, 2022)
Blackberry fruits are appreciated as a source of nutrients and compounds related to benefits to human health. However, they are highly perishable and very susceptible to decay factors. Current methods to improve and maintain blackberry quality are limited in use because of the fruit’s fragile physical properties. Regarding this properties, it has been reported that the activities of certain enzymes are related to senescence and fruit softening processes. This study was aimed to assess the effect of salicylic acid (SA) and chitosan (COS) as preharvest treatments on the physiology related to improving fruit conservation and preserving the marketability index of blackberry fruit. Preharvest treatments were foliar sprayed on blackberry plants at different concentrations. The activities of enzymes superoxide dismutase (SOD), catalase (CAT), phenylalanine ammonia-lyase (PAL), and polygalacturonase (PG) were measured. Total soluble solids (TSS), titratable acidity (TA), TSS/TA ratio, and marketability index were analyzed after 144 hours of storage. The application of SA 3 mM and COS 0.25% treatments presented consistent effects on preserving the marketability index of blackberries by reducing leakage, red drupelet reversion (RDR), and mycelium presence in the fruit. SA application increased SOD, CAT, and PAL activities. Both SA and COS applications decreased PG activity. Our results showed that salicylic acid and chitosan preharvest treatments modified antioxidant defense responses and the activity of the cell wall degrading enzyme PG, which might play a role in improving the shelf life and resistance to decay factors of blackberry fruit without any significant effects on TSS, TA, and TSS/TA ratio.